Safety and long-term outcomes of rotablation in patients with reduced (<50%) left ventricular Ejection Fraction (rEF) (The Rota-REF Study) - Ayoub, Mohamed; Tajti, Péter; Akın, Ibrahim; Behnes, Michael; Schupp, Tobias; Forner, Jan; Omran, Hazem; Westermann, Dirk; Rudolph, Volker; Mashayekhi, Kambis (Journal of Clinical Medicine, 2023)
Clinical outcomes in patients with reduced left ventricular systolic function undergoing rotational atherectomy (RA) for percutaneous coronary intervention (PCI) remain understudied. Our study sought to evaluate the impact of RA-PCI in patients with LV systolic dysfunction on long-term outcomes. Between 2015 and 2019, 4941 patients with reduced LV function (rEF) undergoing PCI (with or without RA) were included in the hospital database. The primary endpoint was in-hospital major adverse cardiovascular and cerebral events (MACCE). The secondary endpoint was 3-year MACCE. In-hospital MACCE rates were significantly higher in RA-PCI compared to standard PCI without RA (PCI) (7.6% vs. 3.9%, p = 0.0009). However, 3-years MACCE rates were similar in RA-PCI and PCI (26.40% vs. 26.6%, p = 0.948). In conclusion, RA-PCI in patients with rEF is feasible, safe, and shows similar long-term results to PCI.